2020
DOI: 10.1016/j.cognition.2020.104460
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the role of conscious and unconscious knowledge in evaluative conditioning

Abstract: Evaluative conditioning (EC) refers to a change in liking of a conditioned stimulus (CS) subsequent to its repeated pairing with a valent stimulus (US). Two studies that bring new light on the highly debated question of the role of awareness in EC were conducted. We developed an innovative method motivated by higher order and integration theories of consciousness to distinguish between the role of conscious and unconscious knowledge about the pairings. On each trial of the awareness test, participants had to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 72 publications
4
42
0
Order By: Relevance
“…valence-memory responses (Stahl et al, 2009). Also replicating previous findings (Waroquier et al, 2020), an EC effect was found for the lowest levels of subjective memory (e.g., low-confidence/Guess responses), although its interpretation is complicated by selection-bias issues. When considered jointly, EC was found to increase with subjective memory only for accurate valence-memory responses.…”
Section: Summary and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…valence-memory responses (Stahl et al, 2009). Also replicating previous findings (Waroquier et al, 2020), an EC effect was found for the lowest levels of subjective memory (e.g., low-confidence/Guess responses), although its interpretation is complicated by selection-bias issues. When considered jointly, EC was found to increase with subjective memory only for accurate valence-memory responses.…”
Section: Summary and Discussionsupporting
confidence: 85%
“…While our interpretation should be considered provisional and open to debate, the pattern itself is clearly reliable. It is consistent not only across the present studies and with our own previous work, but also with novel independent data: The publicly available data from Waroquier et al (2020) allowed us to probe for a comparable pattern in their Experiment 1; the above interaction pattern replicated.…”
Section: Relating Ec and Memorysupporting
confidence: 92%
“…However, typically in these experiments, some participants are aware of (parts of) the regularity, hence some conscious participants or conscious trials need to be excluded. This approach has been employed less often in instrumental conditioning (e.g., Bechara et al, 1997; but see Maia & McClelland, 2004), but has been extensively used in other fields of research on unconscious learning processes, such as evaluative conditioning (e.g., Olson & Fazio, 2001;Jurchis et al, 2020;Waroquier et al, 2020), Pavlovian conditioning (Leganes-Fonteneau et al 2018, visuo-motor sequence learning (e.g., Kobor et al, 2017;Fu et al, 2012) or learning of artificial grammars (e.g., Reber, 1967, in press;Norman et al, 2019). The artificial grammar learning task (AGL) has been one of the most often employed experimental paradigms for investigations on implicit learning.…”
Section: Producing Unawarenessmentioning
confidence: 99%
“…Their task is now to select the string that is the most likely to bring rewards (i.e., the string from the rewarded grammar). Using an awareness measure widely employed in implicit learning and conditioning (e.g., Dienes & Scott, 2005;Norman et al, 2019;Waroquier et al, 2020), we assess the conscious/unconscious status of their structural knowledge, that is, knowledge of which are the structural elements (i.e. the features of the grammars) associated with rewards.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation